REFLEXIÓN SOBRE LA LEY 28 DE 1932_ SETENTA AÑOS DE EMANCIPACIÓN ECONÓMICA DE LA MUJER - Fradique Méndez, Carlos (Revistas ICDP, 2015)
REFLEXIÓN SOBRE LA LEY 28 DE 1932_ SETENTA AÑOS DE EMANCIPACIÓN ECONÓMICA DE LA MUJER